Combined Exploitation of Offshore Wind and Wave Energy in the Italian Seas: A Spatial Planning Approach - Azzellino, Arianna; Lanfredi, Caterina; Riefolo, Luigia; De Santis, Valentina; Contestabile, Pasquale; Vicinanza, Diego (Frontiers in Energy Research, 2019)
The opportunity to co-locate wind and wave energy exploitation is analyzed in the Italian seas grounding on the rationale that benefits are greater when un-correlated resources are combined. The study shows that, although waves and winds are generally strongly correlated, in some conditions their correlation is lower and the combined energy harvesting more interesting. As spatial conflicts of sea use and demand for maritime space are increasing, the development of the marine renewable energy sector needs to be evaluated in the perspective of the cumulative pressures deriving from present activities or expected from future developments. The evaluation of areas of potential conflicts among human activities, environmental vulnerabilities and marine renewable developments may facilitate the early development of mitigation actions and negotiations between stakeholders. In this study the opportunity of co-locating offshore wind turbines and wave energy converters is analyzed through a spatial planning approach. Both the potential for combining different renewable technologies, and the impact associated to such development was considered in the context of the existing pressures (e.g., naval traffic; mariculture activities; submarine cables routes; dredge spoils dumping; offshore activities; windfarms and ocean energy projects) and vulnerabilities (Marine Protected Areas, Key habitat presence) through quantitative indicators. The portion of Tyrrhenian coast south of Elba island, the northern-western Sardinian coast, and the southern Adriatic and Ionian coastal waters appear to be the most suitable sites. Moreover, the study presents a spatial quantitative methodology to identify sites of potential interest for the development of the marine renewable energy sector in the perspective of cost-effectiveness and environmental impact minimization.